Persistent Shoulder Instability and Retained Primitive Reflexes. Addressing a Potential Gap in Adult Musculoskeletal Rehabilitation Care - Ellie Richardson; Ramni Acharya; Peter C Goodwin; Jeremy Lewis (JOSPT Open, 2026)
Using a case of recalcitrant type III shoulder instability, this editorial explores the potentially overlooked link between retained primitive reflexes and persistent musculoskeletal conditions. We explore how incomplete primitive reflex integration may disrupt motor control, compromise dynamic stability, and interact with neurodevelopmental traits like generalized joint hypermobility. Addressing a potential gap in adult musculoskeletal care, we establish a theoretical framework and foundational justification for future research. To investigate this potential paradigm shift, we outline a four-stage research roadmap: mapping existing literature on adult primitive reflexes, validating specific primitive reflex assessment tools in musculoskeletal populations, testing targeted therapeutic integration exercises, and exploring bidirectional symptom relationships. Ultimately, this editorial outlines a clear path forward for decoding neurodevelopmental profiles when traditional physical therapy stalls.